Impact of Low-Carbohydrate Diet Supplemented with Cinnamon Bark and Moringa Seed Oil Extracts on Lipid Profile in Obese Albino Rats - Asfandyar Muhammed Saeed, Aya; Ali M. Faragb, Halgord; Hussain Rasul, Nabil (Kurdistan Journal of Applied Research, 2026)
Dyslipidemia is a preventable cardiovascular risk factor, and low-carbohydrate (LC) diets with or without the addition of bioactive plant oils can modulate lipid metabolism. This study aimed to investigate the impact of an LC diet, alone or in combination with cinnamon bark oil and/or moringa seed oil, on the lipid profiles of obese albino rats. In addition, we determined whether the co-supplementation of these oils could enhance the lipid-modulating effects of an LC diet. Eighty-one obese adult rats were randomly divided into five groups: control, low-carb diet, low-carb diet with cinnamon bark oil extract (LCC), low-carb diet with moringa seed oil extract (LCM), and low-carb diet with cinnamon bark and moringa seed oil extracts (LCCM), and treated for 12 weeks. Total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high- density lipoprotein (HDL), and very low-density lipoprotein (VLDL) levels were determined. Compared with the baseline, following the LC diet intervention, TC declined by 31.45%; it was even higher in groups treated with cinnamon (40.12%) or moringa (47.45%), while mixed oils caused an intermediate decrease (28.68%). Significant reductions of 54.09% were noted with the LC diet, and similar reductions were achieved with the LCC (37.07%) and LCM (48.82%) diets, however, a significantly lower reduction (20.53%) was recorded with the combined oil treatment. TG increased in the control (103.60%) and LC diet (35.80%) groups, was close to baseline in the cinnamon group (2.35%), decreased in the LCM diet group (14.93%), and was slightly lower in the combined oil group (5.34%). VLDL exhibited a similar trend. HDL levels decreased in all intervention groups. Collectively, cinnamon or moringa seemed to augment LC diet-induced amelioration of atherogenic lipids, however, the co-supplementation did not exhibit additive effects, and reductions in HDL require further attention.